1999
DOI: 10.1007/s002640050335
|View full text |Cite
|
Sign up to set email alerts
|

Core decompression in osteonecrosis of the femoral head: risk-factor-dependent outcome evaluation using survivorship analysis

Abstract: The results of core decompression of the femoral head in the treatment of osteonecrosis are analyzed. This study includes 94 hips in 74 patients with a followup time ranging between 18 months and 15 years (average 6 years). There had been no need for further surgery 2 years postoperatively in 85% of the hips with preoperative Steinberg stages 0, I and II when compared with 66% with preoperative stages III, IV and V. At 4 years postoperatively the corresponding figures are 73 compared to 55%; and 6 years postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Limited data exist in the literature documenting successful results in controlled trials at 5-and 10-year follow-up on patients that have undergone core decompression of the hip. Existing studies have indicated promising results that meet or exceed these goals after core decompression, but control groups are often inadequate [1][2][3][4][5][6][7][8][9][10][11]. More rigorous evaluation of core decompression is required to document its true efficacy and resulting cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Limited data exist in the literature documenting successful results in controlled trials at 5-and 10-year follow-up on patients that have undergone core decompression of the hip. Existing studies have indicated promising results that meet or exceed these goals after core decompression, but control groups are often inadequate [1][2][3][4][5][6][7][8][9][10][11]. More rigorous evaluation of core decompression is required to document its true efficacy and resulting cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, core decompression is likely to have poor cost-effectiveness in these cases of latestage disease. Patients with extensive femoral head involvement or a history of long-term steroid use are also likely to demonstrate clinical efficacy below these levels [3][4][5][6][7][8][9][10][11]. The use of core decompression in these subgroups is not supported in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic literature review, Marker et al [12] evaluated the clinical and radiographic outcomes of core decompression in surgeries done before [13][14][15][16][17][18][19][20][21][22] and after 1992 [1,2,10,[23][24][25][26][27][28][29][30][31] (n=1268 and 1337 hips, respectively). The authors demonstrated that in procedures performed before 1992, 41 % of hips required additional surgery after a mean follow-up of 65 months (range, 3 to 216 months).…”
Section: Overall Outcomes Of Traditional Core Decompressionmentioning
confidence: 99%